Phytochemicals analysis of piper betle leaves extracts using FTIR and GC-MS: article - Mohd Latiff, Nor Syahirah; Abdulbari Ali, Sherif (2017)
Piper betle is known as a medicinal plant or herb serves as lead compounds for drug discovery and design. Piper betle may have various phytochemicals which lead to different biological activities used to treat various ailments. The choice of extraction solvents itself may affect the extractable components in the leaves of Piper betle. Therefore, the present study investigates the efficiency of various solvent extracts and the characterization of the bioactive constituents present in the leaf extracts of Piper betle using FTIR and GC-MS. The crude extracts were scanned in the wavelength ranging from 4000-400 cm-1 by using Perkin Elmer Spectrophotometer and the characteristic peaks were detected. For GC-MS analysis, the crude extracts filtered in ash less filter paper with 4 g sodium sulphate and the extract is concentrated to 1 ml by bubbling nitrogen into the solution. The compound detection employed the NIST Ver. 2.0 – Year 2005 library. The biological activities are based on Dr. Duke’s Phytochemical and Ethnobotanical Databases by Dr. Jim Duke of the Agricultural Research Service/USDA. The FTIR spectrum confirmed the presence of phenols, alcohols, alkanes, alkyl halides, carboxylic acids, aromatics, nitro compounds and amines in the three different extracts. The results of the GC-MS analysis provide different peaks determining the presence of phytochemical compounds with different therapeutic activities. The major biochemical component in ethanolic leaves extract is Caryophyllene (25.20%), in acetone leaves extract is àPhellandrene (47.18%) while in chloroform leaves extract is Humulane-1, 6-dien-3-ol (39.15%). Therefore, this study result will make a way for the production of herbal medicines for various ailments by using Piper betle leave.